2020
DOI: 10.26452/ijrps.v11i4.3231
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of twin mix and revamped twin mix in mandibular third molar surgery - A randomised controlled double blinded study

Abstract: Mandibular third molar surgery is one of the most common minor oral surgical procedures performed by oral and maxillofacial surgeons. It is vital to provide the most comfortable postoperative phase to the patient and for this reason dexamethasone, a corticosteroid, is popularly used in various routes. The intraspace injection of dexamethasone mixed with 2% lignocaine and 4% articaine named, Twin Mix and Modified Twin Mix respectively is gaining increasing popularity. 0.5% Centbucridine is a safe alternative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The studies relevant to the use of twin-mix solution are summarized in table 1. 9,10,11, 26,27,28,29,30,31,32 Bhargava D et al first proposed clinical use of the twin mix anaesthesia for mandibular nerve block in 2013 by evaluating this anaesthetic technique and the admixture of drugs through their prospective clinical randomized double-blind study to evaluate latency & efficacy of twin-mix solution & 2% lignocaine with 1:200,000 adrenaline for the transalveolar extraction of impacted mandibular third molars. 9 Gaur S et al conducted a randomized controlled trial evaluating the altered twin mix local anaesthesia using two long acting amide local anesthetic solutions: bupivacaine & ropivacaine with/without 4 mg/ml dexamethasone solution for patients undergoing 3 rd molar surgical extraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies relevant to the use of twin-mix solution are summarized in table 1. 9,10,11, 26,27,28,29,30,31,32 Bhargava D et al first proposed clinical use of the twin mix anaesthesia for mandibular nerve block in 2013 by evaluating this anaesthetic technique and the admixture of drugs through their prospective clinical randomized double-blind study to evaluate latency & efficacy of twin-mix solution & 2% lignocaine with 1:200,000 adrenaline for the transalveolar extraction of impacted mandibular third molars. 9 Gaur S et al conducted a randomized controlled trial evaluating the altered twin mix local anaesthesia using two long acting amide local anesthetic solutions: bupivacaine & ropivacaine with/without 4 mg/ml dexamethasone solution for patients undergoing 3 rd molar surgical extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Authors concluded that RTM can be used as an alternative to TM considering its comparable properties. 28 Bhargava D et al conducted a clinical prospective randomized trial to evaluate post-operative quality of life (QoL) in patients undergoing surgical intervention for isolated vertically undisplaced parasymphysis mandibular fracture with twin mix (TM) anesthetic solution and concluded that the 'TM' solution proves to be more advantageous as compared to the conventional local anaesthetic solution as the former provides an improved clinical outcomes with enhanced the post-operative QoL in patients undergoing open reduction & internal fixation (ORIF under LA) for an undisplaced parasymphysis fractures. 29 This data is in consistence with effects observed with minor oral surgical procedures like transalveolar extractions.…”
Section: Discussionmentioning
confidence: 99%